108k views
4 votes
2m·4b−3a·2n−0.2b·5m+n·5a−5bm+8an

2 Answers

3 votes

Final answer:

To simplify the given expression, we can combine like terms.

Step-by-step explanation:

The given expression is: 2m·4b−3a·2n−0.2b·5m+n·5a−5bm+8an

To simplify the expression, we can combine like terms.

Combining the m terms, we get: 2m(4b - 5b) - 5bm = -m(b) - 5bm = -6bm

Combining the a terms, we get: -3a(2n) + n(5a) = -6an + 5an = -an

Combining the b terms, we get: -0.2b(5m) = -bm

Putting it all together, the simplified expression is: -6bm - an

User Linus Oleander
by
6.0k points
1 vote

Answer:

2bm + 7an

Step-by-step explanation:

Multiply.

8bm - 6an - bm + 5an - 5bm + 8an

Combined like terms:

8bm - 6an - bm + 5an - 5bm + 8an

= 2bm + 7an

User Balachandarkm
by
5.2k points